Counterparty credit limits: An effective tool for mitigating counterparty risk? - Martin D. Gould; Nikolaus Hautsch; Sam D. Howison; Mason A. Porter (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
A counterparty credit limit (CCL) is a limit imposed by a financial institution to cap its maximum possible exposure to a specified counterparty. Although CCLs are designed to help institutions mitigate counterparty risk by selective diversification of their exposures, their implementation restricts the liquidity that institutions can access in an otherwise centralized pool. We address the question of how this mechanism impacts trade prices and volatility, both empirically and via a new model of trading with CCLs. We find empirically that CCLs cause little impact on trade. However, our model highlights that in extreme situations, CCLs could serve to destabilize prices and thereby influence systemic risk.
urn:nbn:de:hebis:30:3-438673
Keywords: 330; Counterparty Credit Limits; Counterparty Risk; Price Formation; Market Design; Systemic Risk